PERAN LEMBAGA KESEJAHTERAAN ANAK DALAM MENANAMKAN PENDIDIKAN KARAKTER TERHADAP ANAK ASUH DI PANTI ASUHAN - Lestari, Winda Anggunita (Civic Education Department, Faculty of Teacher Training and Education, University of Muham, 2016)
This study aims to: 1) Know the implementation of character education; 2) Identify supporting and inhibiting factors in the implementation of character education; 3) Unveil solutions to overcome obstacles faced in the implementation of character education at Nurul Hidayah Orphanage. Approach and type of research used is descriptive qualitative with kind of field research. Research location one month research. Data collection techniques usedare observation, interview and documentation study. Analytical technique using Milles and Huberman model with technique of validity of data of credibility, transferability, dependability, and confirmability. Based on the research results obtained as follows: 1) Character Education at NurulHidayah Orphanage has been strived to develop intellectual and spiritual intelligence with different backgrounds of parenting. 2) Supporting factors in the implementation ofCharacter Education at NurulHidayah Orphanage are: While the inhibiting factors are: the tendency of caregivers to take care of limited to the level of cognitive and religious only; there are still some caregivers who subordinate character education; the varying character of each child and the lack of recognition of the caregiver of each character; and there are still violations of regulations in the Orphanage. 3) Solutions in overcoming the obstacles that occur are: through the direction and evaluation of all Orphanage management; spiritual guidance and counseling; control of the child's intercourse synergistically by the carer.